PENGARUH MARKETING DIGITAL TERHADAP KINERJA PENJUALAN PRODUK UMKM ASTI GAURI DI KECAMATAN BANTARSARI CILACAP - Hendrawan, Andi (STIKS Tarakanita, 2019)
Online marketing is suitable for businesses / businesses that are just starting out. Certainly it is cost effective, because it does not have to hold a place / store to display products / services, can be controlled alone without having to recruit employees, unlimited time or work hours, and has a wide market reach, because online marketing is usually supported by the presence of a website or media social (Facebook, Instagram, WA, etc.) This study is to prove that there is an effect of digital marketing on the sales performance of MSME products in the district of Bantarsari, Cilacap.Research Library (Research Library) is a technique to get theoretical data or secondary data in research. Library research is done by studying books, literature, official documents, notes and transcripts, which are related to research. The study took thirty weeks from the sale of MSME Asti Gauri.the results of the study were the influence of digital marketing on the sales performance of MSME products asti gauri in Bantarsari District, Cilacap